The Barrier to Investment in Early Child Care Development and Education (ECCDE) in Nigeria and Way Forward - TIJANI, Olakunle Abdulgafar; AJAYI, Simon Omoregie (Researchparks Publishing, 2023)
This paper looked at barriers to investment in Early Child Care Development and Education (ECCDE) in Nigeria. Secondary data were employed in the paper presentation and the secondary data were collected from both online and print publications through the content analysis method. The paper identified the poor implementation of national policy on education funding recommendation, insecurity challenges, corruption, non-payment of counterpart funding, revenue leakages, subsidy payment and fall in national revenue as barriers to investment into the Early Child Care Development and Education (ECCDE) in Nigeria. To address these problems, the paper suggested full implementation of the National policy on funding education that states that the government shall allocate a minimum of 26% of the total national budget to the education sector at all levels.